Intratumoural administration of an NKT cell agonist with CpG promotes NKT cell infiltration associated with an enhanced antitumour response and abscopal effect. (31st December 2022) - Prasit, Kef K; Ferrer-Font, Laura; Burn, Olivia K; Anderson, Regan J; Compton, Benjamin J; Schmidt, Alfonso J; Mayer, Johannes U; Chen, Chun-Jen J; Dasyam, Nathaniel; Ritchie, David S; Godfrey, Dale I; Mattarollo, Stephen R; et al.
ABSTRACT: Intratumoural administration of unmethylated cytosine-phosphate-guanine motifs (CpG) to stimulate toll-like receptor (TLR)-9 has been shown to induce tumour regression in preclinical studies and some efficacy in the clinic. Because activated natural killer T (NKT) cells can cooperate with pattern-recognition via TLRs to improve adaptive immune responses, we assessed the impact of combining a repeated dosing regimen of intratumoural CpG with a single intratumoural dose of the NKT cell agonist α-galactosylceramide (α-GalCer). The combination was superior to CpG alone at inducing regression of established tumours in several murine tumour models, primarily mediated by CD8 + T cells. An antitumour effect on distant untreated tumours (abscopal effect) was reliant on sustained activity of NKT cells and was associated with infiltration of KLRG1 + NKT cells in tumours and draining lymph nodes at both injected and untreated distant sites. Cytometric analysis pointed to increased exposure to type I interferon (IFN) affecting many immune cell types in the tumour and lymphoid organs. Accordingly, antitumour activity was lost in animals in which dendritic cells (DCs) were incapable of signaling through the type I IFN receptor. Studies in conditional ablation models showed that conventional type 1 DCs and plasmacytoid DCs were required for the response. In tumour models where the combined treatment was less effective, the addition of tumour-antigen derived peptide, preferably conjugated to α-GalCer, significantly enhanced the antitumour response. The combination of TLR ligation, NKT cell agonism, and peptide delivery could therefore be adapted to induce responses to both known and unknown antigens.